A Debreceni Stomatologiai Klinika kialakulásának története - Kelentey, Barna (Gerundium, 2017)
The foundation history of the Stomatology Clinic in Debrecen. The Hungarian Royal University was opened in the autumn of 1914 and the Medical Faculty was formed in 1918. Already in 1921 the Medical Faculty has applied for the establishment of a Stomatology Clinic from the government, but mainly because of financial reasons the request was turned aside. In the upcoming years the request was repeated several times, without any success. Finally the Medical Faculty has established the Stomatology Polyclinic in the East Wing of the Surgical Clinic, which was opened in 15. February 1935. András Csilléry a dentist of Budapest the former Minister of Public Health and Welfare was called for leader in professional lecturer’s position. In the autumn of 1935 the undergraduate studies begun. In September of 1936 was a new surgery opened to treat the students in the main building of the university. In January of 1937 the school dental care was launched. In the summer of 1940 Csilléry was named university professor and he was elected as head of the Stomatology Clinic, placed in to the East Wing of the Ophthalmic Clinic of the ceremonial event on 30 November 1940.